Perspectives on Batangas State University’s direction toward sustainable culture of quality - Zara, Celso G. (Frontiers in Education, 2025)
This research aims to delve deeper into the concept of quality culture within the context of Philippine higher education institutions (HEIs). Specifically, it examines Batangas State University – Pablo Borbon’s stakeholder perspectives on the prevailing attitudes, beliefs, and behaviors related to quality assurance culture practices, this study seeks to uncover insights into the factors that contribute to the establishment and sustenance of a well-founded quality culture. Through keen analysis, this research aims to provide valuable insights and recommendations for enhancing the quality assurance culture within Philippine HEIs covering the management, leadership, organizational culture, and values, thus, aiming to contribute to the broader discourse on excellence and improvement in higher education.